Methods of Training and Developing Human Resources in Enterprises and some Recommendations - Nguyễn Song Hảo (Journal of Technical Education Science, 2024)
The article focuses on presenting and analyzing methods of training and developing human resources in today's business environment. The theoretical basis section aims to determine the importance of training and human resource development not only internationally but also in Vietnam. The research results section focuses on presenting training and development methods in both short-term and long-term aspects. By evaluating and clarifying these methods, the article hopes to help enterprises have a more general and specific view of how it can be applied to enhance the competency and performance of employees in a work environment. Recommendations in this study include developing online learning applications, building educational games, encouraging continuous learning, learning from real-life experiences, creating an open and friendly working environment, develop soft skills training programs, and build long-term career development programs. This emphasizes the need for a comprehensive and diverse strategy in human resource development to meet the increasing demands of the modern business environment.